2010
DOI: 10.1007/s10549-010-1042-5
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the urokinase receptor mRNA splice variant uPAR-del4/5 affects tumor-associated processes of breast cancer cells in vitro and in vivo

Abstract: Conclusions: We demonstrate that the uPAR-del4/5 mRNA splice variant mediates tumorrelevant biological processes in vitro and in vivo. Our results thus illustrate how tumorspecific alternative splicing can distinctly impact the biology of the tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Transfected cells were also characterized by immunocytofluorescence [22]. The intensity of rab31 immunocytostaining of transfected cells was in parallel with the results obtained by Western blot analysis (data not shown).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Transfected cells were also characterized by immunocytofluorescence [22]. The intensity of rab31 immunocytostaining of transfected cells was in parallel with the results obtained by Western blot analysis (data not shown).…”
Section: Resultssupporting
confidence: 67%
“…One of these splice variants, uPAR-del4/5, encodes a molecular form of uPAR which lacks domain DII of uPAR and does not interact with its ligand uPA [21,22]. Quantification of mRNA levels of uPAR-del4/5 in tumor tissues revealed that higher uPAR-del4/5 expression - similar to rab31 - is associated with shorter disease-free survival of breast cancer patients [15,21,49].…”
Section: Discussionmentioning
confidence: 99%
“…24,26 This truncated receptor may, nevertheless, still be GPI-anchored on the cell surface as the signal peptide and the GPI anchorage site remain intact. 27,28 At present, however, it remains to be proven whether this variant is expressed in vivo at the protein level and is secreted in detectable amounts into the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas wild-type uPAR consists of three structurally homologous domains, in the uPAR-del4/5 variant the complete domain II of uPAR is deleted, and the uPAR-del4/5 protein does not interact with either of its ligands uPA or vitronectin [17]. However, in breast cancer cells the overexpression of the uPAR-del4/5 protein profoundly affects the in vitro invasion capacity of cells through a Matrigel matrix, the adhesion to extracellular matrix proteins and also lung colonization in an in vivo metastasis model.…”
Section: Introductionmentioning
confidence: 99%